Hydrothermally Treated Chitosan Hydrogel Loaded with Copper and Zinc Particles as a Potential Micronutrient-Based Antimicrobial Feed Additive - Rajasekaran, Parthiban; Santra, Swadeshmukul (Frontiers in Veterinary Science, 2015)
Large-scale use of antibiotics in food animal farms as growth promoters is considered as one of the driving factors behind increasing incidence of microbial resistance. Several alternatives are under investigation to reduce the amount of total antibiotics used in order to avoid any potential transmission of drug resistant microbes to humans through food chain. Copper sulfate and zinc oxide salts are used as feed supplement as they exhibit antimicrobial properties in addition to being micronutrients. However, higher dosage of copper and zinc (often needed for growth promoting effect) to animals is not advisable because of potential environmental toxicity arising from excreta. Innovative strategies are needed to utilize the complete potential of trace minerals as growth promoting feed supplements. To this end, we describe here the development and preliminary characterization of hydrothermally treated chitosan as a delivery vehicle for copper and zinc nanoparticles that could act as a micronutrient based antimicrobial feed supplement. Material characterization studies showed that hydrothermal treatment makes a chitosan hydrogel that re-arranged to capture the copper and zinc metal particles. Systemic antimicrobial assays showed that this chitosan biopolymer matrix embedded with copper (57.6 μg/ml) and zinc (800 μg/ml) reduced the load of model gut-bacteria (target organisms of growth promoting antibiotics) such as Escherichia coli, Enterococcus faecalis, Staphylococcus aureus and Lactobacillus fermentum under in vitro conditions. Particularly, the chitosan/copper/zinc hydrogel exhibited significantly higher antimicrobial effect against L. fermentum, one of the primary targets of antibiotic growth promoters. Additionally, the chitosan matrix ameliorated the cytotoxicity levels of metal supplements when screened against a murine macrophage cell line RAW 264.7 and in TE-71, a murine thymic epithelial cell line. In this proof of concept study, we show that by using chitosan as a delivery platform, micronutrient-based metal feed additives could be used to minimize the undesirable levels of microbial population without causing significant cytotoxic effect under in vitro conditions. These findings provide the platform for further studies in target animal models to quantify the required physiological concentrations of copper and zinc when delivered via a chitosan hydrogel platform to elicit a growth promoting effect without causing any toxicity.